Analyzing hysteresis loops via coupling factors for inductive sensing technique - Tasnim, Rumana; Khan, Sheroz; Mohamed, M.; Arshad, Atika; Saquib, Nazmus (2012)
The advancement of magnetic sensors in biomedical sector has led toward an immense range of applications. Inductive coupling link has been validated as the most suitable and efficient means for wireless transfer of signal where coupling coefficient plays a crucial role to determine the strength of the transmission in power transfer. In view of that an urgent investigation of the relative magnetism of magnetic and nonmagnetic materials are required. This paper aims to analyse the magnetization effect of a magneto-inductive sensor based on the inductive coupling technique in low frequency range for different values of coupling coefficient. The results have appeared to show different magnetization behavior with the variation of coupling factors. The obtained hysteresis loops for different coupling factors are evaluated in this paper for suitable application.